Karakter Fisik dan Sensoris Produk Hasil Restrukturisasi Buah Nangka (Artocarpus heterophylla L.) dan Sawo (Manilkara achras (Mill.) Fosb) Selama Penyimpanan Beku - Sri Raharjo; Suparmo Suparmo; Wahyu Supartomo; Zaki Utama (agriTECH, 2002)
A model fruit product was prepared using fresh tropical fruits puree (jackfruit and sapodilla) and restructured using calcium-alginate gel forming methods (internal setting). Restructured fruit products were evaluated for texture (hardness), color, pH, and sensory properties after 0,1,2, and 3 months frozen storage at -15ºC. No significant change for pH was observed over the frozen storage period (3 months at -15ºC).